Penerapan Berkumur Air Matang untuk Menurunkan Tingkat Rasa Haus Pasien Gagal Ginjal Kronis: Studi Kasus - Marchellany, Cantika; Purwanti, Okti Sri; Prastiwi, Yohana Ika (Universitas Pahlawan Tuanku Tambusai, 2024)
In the fluid restriction program, patients with chronic renal failure will cause thirst. The patient controls this thirst by drinking. As a result, if it is not controlled, it can increase the accumulation of fluids which can cause edema and shortness of breath. Thirst needs to be controlled so that patients can adhere to fluid restriction programs and reduce the risk of complications. One of the ways used to overcome thirst is by gargling boiled water. This case study aims to obtain an overview and results of the application of gargling with boiled water to reduce thirst in CRF patients who are undergoing hemodialysis. The research method used a case study with a nursing care approach in the application of evidence-based nursing practice to one managed patient who was given an intervention by gargling boiled water for three meetings. The application of gargling with boiled water can reduce the level of thirst in chronic kidney failure patients undergoing hemodialysis from moderate thirst (4-6) to mild thirst (1-3), with an average length of time to hold thirst for 45 minutes.